Climate change amplifies neurotoxic methylmercury threat to Asian fish consumers - Mengjie Wu; Xinda Wu; Alfonso Saiz-Lopez; Paul J. Blanchfield; Hongqiang Ren; Huan Zhong (Proceedings of the National Academy of Sciences, 2025)
Climate change is intricately influencing the accumulation of neurotoxic methylmercury (MeHg) in human food webs, potentially leading to uneven exposure risks across regions. Here, we reveal that climate change will elevate MeHg risks in China, with implications for regional inequalities in Asia through a climate-mercury-food-health nexus. Using a compiled fish mercury dataset from 13,000 samples and machine learning, we find that freshwater wild fish—an essential component of the Asian diet—is an underappreciated MeHg source. Specifically, MeHg concentrations in freshwater wild fish are 2.9 to 6.2 times higher than in freshwater farmed fish and 1.7 times higher than in marine wild fish. Individual climate factors influence MeHg accumulation differently, while their combined effects significantly increase MeHg concentrations in freshwater wild fish. Under SSP2–4.5 and SSP5–8.5 by 2031 to 2060, national average MeHg concentrations in freshwater wild fish are projected to increase by about 60%, adding a maximum annual economic loss of US$18 million (2022 USD) from intelligence quotient decrements in Chinese newborns. This loss may vary regionally within China and among Asian countries, disproportionately affecting less developed areas. Coordinating climate action with mercury emission reduction strategies could mitigate these overlooked regional risks, reduce regional inequalities in food safety, and ultimately contribute to sustainable development.